2014
DOI: 10.1097/brs.0000000000000164
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Adjacent Segment Disease Requiring Surgery After Lumbar Spinal Fusion

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(68 citation statements)
references
References 28 publications
2
63
2
1
Order By: Relevance
“…A previous FE analysis has shown that removing the posterior complex during decompression with posterolateral fusion could cause potential adjacent segmental instability [10]. Moreover, PLIF has been reported to be more rigid than posterolateral fusion [28, 29], and hence patients who undergo are likely to experience a higher incidence of ASD than those who underwent posterolateral fusion [30]. However, most previous PLIF FE analyses have neglected the importance of posterior complex and focused on the altered biomechanical behavior in the fused lumbar spine with spinal fixators and cages [16, 17, 24, 28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…A previous FE analysis has shown that removing the posterior complex during decompression with posterolateral fusion could cause potential adjacent segmental instability [10]. Moreover, PLIF has been reported to be more rigid than posterolateral fusion [28, 29], and hence patients who undergo are likely to experience a higher incidence of ASD than those who underwent posterolateral fusion [30]. However, most previous PLIF FE analyses have neglected the importance of posterior complex and focused on the altered biomechanical behavior in the fused lumbar spine with spinal fixators and cages [16, 17, 24, 28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…ASD is one reason reoperations are necessary and have a higher incidence in elderly patients. 22 The probability of undergoing a revision surgery for ASD was 5.8% at 5 years and 10.4% and 10 years postoperatively. 22 The prevalence of ASD requiring reoperation in patients older than 60 years of age was 21.9% at 10 years postoperatively.…”
Section: Discussionmentioning
confidence: 93%
“… 22 The probability of undergoing a revision surgery for ASD was 5.8% at 5 years and 10.4% and 10 years postoperatively. 22 The prevalence of ASD requiring reoperation in patients older than 60 years of age was 21.9% at 10 years postoperatively. 22 PLIF procedures showed significantly lower survival rates than PLF procedures.…”
Section: Discussionmentioning
confidence: 93%
“…Lumbar fusion surgery is the primary therapy for multi-level lumbar degenerative disease, but complications may occur, especially acceleration of ASD [20, 21]. Following improved knowledge of lumbar motion function, dynamic stabilization techniques developed quickly, and posterior dynamic stabilization has been accepted and used by more and more spine surgeons.…”
Section: Discussionmentioning
confidence: 99%